Ash Shutbah: A possible impact structure in Saudi Arabia. (October 2014) - Gnos, Edwin; Hofmann, Beda A.; Schmieder, Martin; Al‐Wagdani, Khalid; Mahjoub, Ayman; Al‐Solami, Abdulaziz A.; Habibullah, Siddiq N.; Matter, Albert; Alwmark, Carl
Abstract We have investigated the Ash Shutbah circular structure in central Saudi Arabia (21°37′N 45°39′E) using satellite imagery, field mapping, thin‐section petrography, and X‐ray diffraction of collected samples. The approximately 2.1 km sized structure located in flat‐lying Jurassic Tuwaiq Mountain Limestone has been nearly peneplained by erosional processes. Satellite and structural data show a central area consisting of Dhruma Formation sandstones with steep bedding and tight folds plunging radially outward. Open folding occurs in displaced, younger Tuwaiq Mountain Limestone Formation blocks surrounding the central area, but is absent outside the circular structure. An approximately 60 cm thick, unique folded and disrupted orthoquartzitic sandstone marker bed occurring in the central area of the structure is found 140 m deeper in undisturbed escarpment outcrops located a few hundred meters west of the structure. With exception of a possible concave shatter cone found in the orthoquartzite of the central area, other diagnostic shock features are lacking. Some quartz‐rich sandstones from the central area show pervasive fracturing of quartz grains with common concussion fractures. This deformation was followed by an event of quartz dissolution and calcite precipitation consistent with local sea‐ or groundwater heating. The combination of central stratigraphic uplift of 140 m, concussion features in discolored sandstone, outward‐dipping concentric folds in the central area, deformation restricted to the rocks of the ring structure, a complex circular structure of 2.1 km diameter that appears broadly consistent with what one would expect from an impact structure in sedimentary targets, and a possible shatter cone all point to an impact origin of the Ash Shutbah structure. In fact, the Ash Shutbah structure appears to be a textbook example of an eroded, complex impact crater located in flat‐lying sedimentary rocks, where the undisturbed stratigraphic section can be studied in escarpment outcrops in the vicinity of the structure.